Effect of ammonia concentration in the vapor mixture flowing out of the rectifier on the evaporator performance of the ammonia-water absorption refrigeration machine (Damascus University Journal for engineering sciences, 2021)
Absorption refrigeration machines are receiving a great attention from researchers and manufacturers worldwide since they utilize thermal energy that can be obtained from the sun, in addition to that, their working fluids do not harm the environment. One of the most common working fluids is the ammonia-water solution which allows us to obtain temperature as low as -60 [ºC]. The main disadvantage of this solution is that the boiling temperatures of pure water and ammonia at certain pressure are close so that water vapor is released in addition to ammonia vapor in the desorber (generator). Therefore, a rectifier is installed in the cycle to obtain a mixture with a determined value of ammonia mass concentration. Because the working fluid flowing into the evaporator is not pure refrigerant (ammonia) but a mixture of ammonia and water, temperature during evaporation increases at constant pressure. The target of this research is to study the effect of ammonia concentration in the ammonia-water mixture flowing into the evaporator on its performance. It has been found that for ammonia mass concentration of 99% and allowing the temperature at the outlet of the evaporator to increase only 3 [ºC] above the temperature at its inlet which is 0 [ºC], vapor quality increases to 0.921, while for ammonia mass concentration of 99.9% vapor quality is 0.992. These values increase for the case of evaporator inlet temperature of -30 [ºC] so that they become 0.935 for ammonia mass concentration of 99%, and 0.993 for ammonia mass concentration of 99.9%. Therefore, most of the evaporation process is accomplished within a small increase in temperature. It has also been found that the lower the evaporator temperature, the higher the vapor quality at the outlet of the evaporator for certain determined value of ammonia mass concentration and determined increase in the temperature during the evaporation.
Keywords: Absorption refrigeration machine; Ammonia-water solution; Partial condensation rectifier; Mass concentration; Start boiling temperature; Start condensation temperature; Vapor quality